Fast quantitative susceptibility reconstruction via total field inversion with improved weighted L0 norm approximation. (27th February 2019) - Zhang, Li; Chen, Xi; Lin, Jianzhong; Ding, Xinghao; Bao, Lijun; Cai, Congbo; Li, Jing; Chen, Zhong; Cai, Shuhui
Abstract : Quantitative susceptibility mapping (QSM) is a meaningful MRI technique owing to its unique relation to actual physical tissue magnetic properties. The reconstruction of QSM is usually decomposed into three sub‐problems, which are solved independently. However, this decomposition does not conform to the causes of the problems, and may cause discontinuity of parameters and error accumulation. In this paper, a fast reconstruction method named fast TFI based on total field inversion was proposed. It can accelerate the total field inversion by using a specially selected preconditioner and advanced solution of the weighted L 0 regularization. Due to the employment of an effective model, the proposed method can efficiently reconstruct the QSM of brains with lesions, where other methods may encounter problems. Experimental results from simulation and in vivo data verified that the new method has better reconstruction accuracy, faster convergence ability and excellent robustness, which may promote clinical application of QSM. Abstract : Quantitative susceptibility reconstruction is accelerated by fast total field inversion method (fast TFI). Benefitting from the advanced solution of weighted L0 regularization and some special simplifications, fast TFI can efficiently reconstruct quantitative susceptibility maps of both healthy and pathological brains. The advantages of fast TFI over previous methods lie in better reconstruction accuracy, faster convergence ability and excellent robustness.